PENGETAHUAN ERGONOMI TERHADAP POSTUR TUBUH DALAM PRAKTEK DENTAL - -, ulliana; Nur Sa’adah, Rifa; Puspitawati, Yuli (Jurnal Terapi Gigi dan Mulut, 2024)
Background: Occupational Safety and Health (K3) is an effort to protect workers and others who are in the workplace to avoid potential hazards or occupational accidents that can occur. Body posture is one of the things that greatly affects a person's work productivity and is one of the most important factors because posture can cause musculoskeletal disorder. Ergonomics is the study of equipment and workspace design to maximize productivity and minimize worker fatigue and pain. The purpose of the study was to determine the level of ergonomic knowledge of posture in dental practice at dental therapists. This type of research is descriptive quantitative with a cross-sectional research design. The study population amounted to 34 respondents. Sampling by means of total sampling. Data collection instrument using questionnaire and observation using the Ovako Working Posture Analysis System (OWAS) method. Data analysis using univariate analysis uses SPSS to derive frequency distribution and proportions. The results of the study found that 34 respondents had a level of ergonomic knowledge of body posture in the good category of dental practice. Posture in the back posture category with a straight / upright indicator of 34 (100%), the arm posture category with the indicator of left and right arms above the shoulder by 12 (35.2%), and the category of foot posture that is often done by respondents is the indicator of sitting and walking by 33 (97.0%) and standing and resting on both straight legs by 31 (91.1%). In conclusion, the knowledge of dental and oral therapists regarding ergonomics towards good category posture.